Advance directives and suicidal behaviour. (7th September 2010) - Kapur, Navneet; Clements, Caroline; Bateman, Nick; Foëx, Bernard; Mackway-Jones, Kevin; Huxtable, Richard; Gunnell, David; Hawton, Keith
Abstract : How do you manage a patient who has self harmed but states she doesn't want life saving treatment? Anthony David and colleagues draw on the case of Kerrie Wooltorton to discuss the difficulties, and in an accompanying article Navneet Kapur and colleagues consider the validity of advance directives